La percepción de la pobreza bajo el ángulo de la teoría de la vinculación: Naturalización, culpabilización y victimización - Paugman, Serge (Revista de Sociología, 2016)
Naturalization, criminalization and victimization are three forms of perception of poverty inevitably present in all societies. Beyond the factors of change generally taken into account, this article inquires more specifically into the modes of regulation of social bonds which can be analyzed using a typology of attachment configurations as a starting point.